Chemical composition of fog water at Mt. Tateyama near the coast of the Japan Sea in central Japan - Watanabe, Koichi; Honoki, Hideharu; Iwama, Shinji; Iwatake, Kaname; Mori, Shunya; Nishimoto, Daiki; Komori, Shizuka; Saito, Yukiko; Yamada, Hirotsugu; Uehara, Yoshitoshi (ERDKUNDE, 2011)
Measurements of the chemical composition of fog water at Murododaira (altitude, 2,450 m), near the summit of Mt. Tateyama near the coast of the Japan Sea, were performed during the summers (late July and August) of 2004 and 2008 and the autumns (September and early October) of 2008 and 2009. Fog water was also sampled at Bijodaira (altitude, 977 m) and Midagahara (altitude, 1,930 m), on the western slope of Mt. Tateyama, in the autumn of 2009. Strong acidic fogs (pH < 4) were observed during the summer and autumn. The mean ionic concentration at Murododaira in the summer of 2008 was higher than that in the autumn. The air mass at Murododaira was derived primarily from the polluted regions of Asia in the summer of 2008, and the trans-boundary air pollution might have contributed to fog water acidification. On the other hand, acidic fogs might have been produced mainly by pollutants from central and western Japan in 2004. The non-sea-salt sulfate (nssSO42-) concentration was usually higher than the NO3- concentration at Murododaira, and the chemical characteristics are different from that of fog water near the industrial regions of Japan where NOX is the main air pollution. The average ratio of NO3-/nssSO42- in fog water was relatively high in the summer of 2004. The mean NO3-/nssSO42- ratio was significantly low during the autumn of 2008 when the air mass usually came from Asia. Relatively high concentrations of sea-salt components were detected at Murododaira during the autumn of 2009. The acidity of fog water was higher at Murododaira than at Bijodaira and Midagahara. The deposition flux of acidic species by fog water seemed to be higher at Murododaira than at the lower sites.